Dentine sensitivity risk factors: A case–control study (2023)
Objective: To identify the clinical and psychological risk factors associated with dentine hypersensitivity (DH) in order to provide an early diagnosis and preventive therapy. Materials and Methods: A nested case-control study was design between 2011 and 2012. A total of 61 DH cases and 122 controls participated in this investigation. Cases and controls were matched for sex, group of age and socioeconomic status in a ratio of 1:2. DH to different stimuli such as cold, heat, acid, and sweet was asked in patient interviews, and dental examinations were used to detect DH. Clinical and psychological risk factors such as dental hygiene, periodontal disease, acid diet, alcohol consumption, psychological stress, and psychopathological symptoms were inquired. Psychological stress was measured through the PSS-10 and psychopathological symptoms were evaluated by SCL-90-R in Spanish. Descriptive and univariate binary logistic regression analysis were performed to estimate the association between clinical and psychological risk factors and the presence of DH. Results: Toothpaste abrasivity (odds ratio [OR] 1.881, 95% confidence interval [CI] 1.010-3.502, P = 0.045), gingival recession (OR 2.196, 95% CI 1.020-4.728, P = 0.041), and periodontal therapy (OR 5.357, 95% CI 2.051-13.993, P < 0.001) were associated with DH. Subjects with perceived stress (OR 1.211, 95%, CI 0.518-2.833, P = 0.658), obsessive-compulsive (OR 1.266, 95%, CI 0.494-3.240, P = 0.623) and hostility (OR 1.235, 95%, CI 0.507-3.007, P = 0.642) symptoms had a clinical greater odd of DH. Conclusion: Oral hygiene products and periodontal conditions are important risk factors for DH. Individuals with perceived stress, obsessive-compulsive, and hostility symptoms may increase a clinical risk for this entity. Targeting to dental counseling focused on oral hygiene products, periodontal therapy and a psychological evaluation may be promising in DH prevention. © 2016 European Journal of Dentistry.